Effect of head teachers support for teachers professional development on inclusive education implementation - Douglas Isigi Shiwani; Jeremiah Kalai; Winston Akala; Jane Gatumu (STKIP Singkawang, 2021)
The study investigated the effect of head teachers’ support for teachers’ professional development on inclusive education implementation. Bartalanffy (1969) open systems advocates for head teachers to utilize management initiatives with partnerships to implement inclusive education. Descriptive survey was applied, and Chi-square tested the null hypothesis. Questionnaires were administered to 71 head teachers and 297 teachers, supplemented by document analysis. Interview was used on eight Quality Assurance Standards Officers (QASOs) and four Education Assessment Resource Centre Officers (EARCs). Quantitative data was coded and analyzed using descriptive statistics, and presented in frequency tables and bar graphs. Qualitative data was coded, transcribed and presented in narrative form. Both quantitative and qualitative data findings were discussed in juxtaposition with confirming or refuting the research evidence, and reinforcing the interpretation. The Chi-square results established that there was relationship between head teachers’ support for teachers’ professional development with inclusive education implementation. However, majority of head teachers and teachers lacked specialized skills in assessment of diverse learners, 77.5% and 80.5%; behaviour management, 74.7% and 79.1%; differentiated teaching, 80.3% and 81.1%, derailing teachers’ productivity and learners’ performance. Therefore, it was recommended that head teachers in collaboration with multi-agencies facilitate teachers’ inclusive education training in order to effectively implement inclusive education.